Power Marine Stewardship Council (MSC) dalam Mewujudkan Program Sea Lion Exclusion Devices (SLED) di Australia Tahun 2007-2012 - Chandra Putra, I Putu Gili Bestar; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT   The bycatch of marine biota species, especially the Sea Lion that interacts with the Fishing Industry, has become an transnational issue. Australia with endemic sea lion species that often interacts with lobster fisheries, trying to minimize or stop the impact.That why Australia needs help from various elements to implement it. MSC was invited to discuss and certify mitigation efforts for the Australian Sea Lion and Australian Fisheries Industry certification. The locus of this research is 2007-2012. This research uses the concept of Power of NGOs and Three Faces of Power theory. The results of the study illustrate that in this case, there is a power source owned by MSC so that can be invited by Australia to discuss this bycatch issue. The source of power is information that has been previously owned and strengthened by information from the epistemic community that affects the policy making process.   Keywords :  Marine Stewardship Council, Bycatch, Power of NGO, Three Faces of Power